Fish farms and land confiscation in the Ayeyarwady delta: History, impact and prospects for restitution - Mark, SiuSue (Michigan State University, 2017)
This policy brief draws on qualitative fieldwork conducted in Maubin township, Ayeyarwady – one of the most important locations for aquaculture (fish farming) in Myanmar. Local officials, community members, civil society leaders and operators of large fish farms were interviewed about the history and consequences of land confiscation for use in aquaculture, and the prospects for land restitution.